Escaping Slavery and Building Diasporic Communities in French Soudan and Senegal, ca. 1880-1940 - Rodet, Marie (The International journal of African historical studies, 2015)
Notable exceptions for Western Sudan are Roberts, Klein, and Peterson, but their analyses primarily looked at the exodus of formerly enslaved populations returning to their region of origin.13 This article examines those formerly enslaved populations who did not return to their regions of origin but established new communities elsewhere as a way to secure their freedom and survival. Migration networks and diasporic practices secured permanent flows of peoples, goods, and experiences back and forth between Mali and Senegal and intermarriages over several generations between the two colonies.136 As noted by Peterson for returnees in Wasulu, the scattering and migration of freed slaves in Western Sudan resulted in profound social mixing that had longstanding effects on religious and marriage practices as well as ethnic identities.137 Conclusion In this article I have demonstrated how dispersed populations from southern Mali were able to build new diasporic social spaces along ancient slave trade routes, stretching from southern Mali to Senegal, in order to overcome the legacies of slavery.